CREATIVE ACTIVITIES WITH WASTE MATERIALS IN TRAINING OF FUTURE TEACHERS - OLEKSAKOVA, Monika (Trends in education, 2011)
The starting point of this paper are continuously increasing demand for separation, recycling waste and increasing demands on management education in the light of these requirements. Teacher education in this is the most important element which determines not only its course, but also its quality. We decided therefore to strengthen future teachers preparing students for preschool and elementary education and students of the subjects tutorage technical orientation for their future vocation through creative activities with waste material, within which, thus acquire a basic understanding of the creative tasks, the waste materials As well as the possibilities of further aesthetic and especially educational use.
Keywords: Waste material; the teacher; students.